Hak-Hak Masyarakat Adat, Pengakuan dan Demokrasi: Pembelajaran dari Desa Pulau Sarak Kabupaten Kampar - Ishak Ishak; Auradian Marta; Hasanuddin Hasanuddin; Rury Febrina (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
Indigenous peoples as state entities have constitutional rights that must be fulfilled. However, the existence of indigenous peoples today is still marginalized so they are not much involved in the administration of government. Departing from this empirical phenomenon, this study aims to describe the recognition of indigenous peoples' rights and the village government's strategy in implementing the recognition of indigenous peoples' rights. This study uses a qualitative approach with sources of information from the village government, traditional leaders, and the local government of Kampar Regency. From this research, it is found that the rights of indigenous peoples are recognized in the form of (1) having autonomous rights over their customary communities; (2) the right to manage their ulayat; (3) the right to develop and preserve their customs. Meanwhile, the village government's strategy in implementing the rights and recognition of indigenous peoples is to collaborate with traditional institutions in the administration of government and the implementation of economic, social, political, and cultural life. This study concludes that the democratization process has brought positive changes to the recognition and protection of indigenous peoples' rights.